Reading the Fourfold Gospel From the Two Creation Stories in Genesis: A Creation Theological Understanding of the Fourfold Gospel for Holistic Mission. (July 2020) - Yun, Joel Suh-Tae
The Fourfold Gospel of regeneration, sanctification, divine healing, and the Second Coming was introduced to Korea in the early 20th century and played a crucial role in developing the Korea Holiness Churches. It seems, however, that the previous understanding of the Fourfold Gospel has some limitations in helping Christians to participate in missio Dei . Because missiological hermeneutics of the Fourfold Gospel has focused mainly on the theology of redemption, it has frequently led to a narrow understanding of missio Dei . Through the reading of the two creation stories in Genesis, we can recognize that God's creative works already have redemptive meanings and that His redemptive works already have creative/creational meanings. In this sense, it is also possible to see the Fourfold Gospel from a creation theological perspective. This understanding may positively motivate Christians to participate in missio Dei to restore and complete God's creation as his vicegerents and stewards.